Athlete’s heart in a Brazilian paralympic judo team. Case series study - Oliveira Filho, Japy Angelini; Barros, Maria Beatriz Monteiro; Salles, Ana Fátima; Echenique, Leandro Santini; Campos Filho, Orlando; Póvoa, Rui Manoel Santos (São Paulo Medical Journal, 2018)
BACKGROUND: Athlete’s heart is a term describing the cardiovascular effects of long-term conditioning among highly trained athletes. It is a variation of normal standards. DESIGN AND SETTING: Case series study at the cardiology division of a public university hospital. METHODS: We studied 14 visually handicapped paralympic athletes (8 men) in the national judo team. They were 26.3 ± 6.4 years old, with body mass index 25 ± 14, and had been practicing judo for 9.2 ± 7.9 years. Clinical evaluations, electrocardiograms, exercise testing and echocardiograms were performed by independent observers. RESULTS: Signs of athlete’s heart were found in all athletes, comprising left ventricular hypertrophy (5 cases), sinus bradycardia (5), T-wave juvenile pattern (3), T wave juvenile pattern (3), left atrial hypertrophy (2) and increased left ventricular volume (9 cases; 62.22 ± 6.46 ml/m2). There were very strong correlations between left ventricular mass/body surface and endurance time (r: 0.91) and estimated peak oxygen uptake (r: 0.8). The correlations between left ventricular internal diastolic dimension and endurance time (r: 0.91) and estimated peak oxygen uptake (r: 0.8) were strong. Despite increased left ventricular dimensions (4 cases), atrial dimensions (1) and relative wall thickness (4), all athletes had normal left ventricular mass/body surface (89.98 ± 21.93 g/m²). The exercise testing was normal: exercise duration 706 ± 45 seconds and estimated peak oxygen uptake 62.70 ± 9.99 mlO2/min. CONCLUSIONS: Signs of athlete’s heart were seen frequently in the paralympic judo team. These demonstrated the presence of mild cardiac adaptations to training.